2019
DOI: 10.1096/fj.201900862r
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostus lactone suppresses osteoclast differentiation by regulating NFATc1 and inhibits osteoclast activation through modulating migration and lysosome function

Abstract: Excessive osteoclast activity can lead to an imbalance between the synthesis and breakdown of bone, with pathologic consequences that include osteoporosis and periodontitis. Thus, controlling osteoclast differentiation and function has significant therapeutic implications. In this study, we investigated the effects of dehydrocostus lactone (DL) on osteoclast differentiation and activation and elucidated the possible mechanisms underlying these processes. DL suppressed osteoclast differentiation by reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Osteoclasts are unique cells that play a critical role in maintaining bone homeostasis and normal bone density. It has also been demonstrated that osteoclasts are crucial in osteoporosis (Jacome-Galarza et al, 2019;Lee et al, 2019). Excessive osteoclastogenesis and bone resorption result in changes in trabecular bone mass and microstructure, leading to the potential risk of fracture (Tella and Gallagher, 2014;Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclasts are unique cells that play a critical role in maintaining bone homeostasis and normal bone density. It has also been demonstrated that osteoclasts are crucial in osteoporosis (Jacome-Galarza et al, 2019;Lee et al, 2019). Excessive osteoclastogenesis and bone resorption result in changes in trabecular bone mass and microstructure, leading to the potential risk of fracture (Tella and Gallagher, 2014;Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Then, nuclear factor of activated T cells cytoplasmic 1 (NFATc1), the main transcription factor that regulates osteoclast differentiation, will be triggered to stimulate preosteoclast maturation (Jiang et al, 2019;Zhao K. et al, 2019). Maturational osteoclasts, which are characterized by tartrate-resistant acid phosphatase (TRAP) expression, can generate actin-bound sealing zones for attaching to the surface of bone, and osteoclasts then release proteolytic enzymes, such as cathepsin K (CTSK), which promote resorption pit formation (Lee et al, 2019;Zhao X. et al, 2019). Excessive osteoclastogenesis and bone resorption result in changes in trabecular bone mass and microstructure, leading to the potential risk of fracture; this indicates the need to find therapeutic approaches to prevent osteoporosis (Eriksen et al, 2014;Chen et al, 2019;Jacome-Galarza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was reported that DL inhibits RANKLinduced osteoclastogenesis by negatively regulating NFATc1 (16). In order to investigate the DL-mediated inhibition of NFATc1, the effect of DL on NF-B that plays an essential role http://bmbreports.org BMB Reports in NFATc1 expression was explored.…”
Section: Inhibits Rankl-induced Nf-b Activation By Regulating Ikkmentioning
confidence: 99%
“…Dehydrocostus lactone (DL) has been reported to possess antioxidant activity (14) and protect osteoblast cell line MC3T3-E1 against oxidative stress and dysfunction (15). Recently, we reported that DL inhibits osteoclast differentiation by regulating NFATc1, and attenuates osteoclast activation by modulating migration and lysosome function (16). However, the mechanism of DL-mediated regulation of RANKL-induced NFATc1 activation has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that NRF2 is crucial to OC activity, but the underlying mechanism of NRF2 in regulating OC activity remains unclear [123]. Increased p38 MAP kinase activity but not the NF-kB pathway was associated to ROS elevation in NFR2 knockout mice [124][125][126][127]. Moreover, NRF2 also represses OC activity via regulating the activity of NFATc1, which is the master transcription factor for osteoclastogenesis [124,128].…”
Section: The Effects Of Nrf2 On Ocmentioning
confidence: 99%